2022
DOI: 10.1155/2022/5216786
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ACLY Disrupts Histone Acetylation and IL-10 Secretion in Trophoblasts, Which Inhibits M2 Polarization of Macrophages: A Possible Role in Recurrent Spontaneous Abortion

Abstract: Changes to macrophage polarization affect the local microenvironment of the placenta, resulting in pathological pregnancy diseases such as recurrent spontaneous abortion (RSA). Macrophages are in close contact with trophoblasts during placental development, and trophoblast-derived cytokines are important regulators of macrophage polarization and function. Histone acetylation can affect the expression and secretion of cytokines, and ATP citrate lyase (ACLY) is an important factor that regulates histone acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…To further systematically understand the immunomodulatory activities that decidua-DEGs and placenta-DEGs were involved in, we performed immune function enrichment analysis by CluGO, which displayed that these DEGs were mainly closely related to macrophage activity, such as affecting macrophage tolerance induction, regulation of macrophage antigen processing and presentation as well as macrophage activation. It has been confirmed that DSC-conditioned medium (CM) can promote macrophage survival and induce typical phenotype of decidual macrophages, and that DSC-CM also inhibit the proinflammatory effects of granulocyte-macrophage colony- (43). From the above studies we could project that DSCs and trophoblasts exerted significant effects on the phenotype and function of decidual macrophage.…”
Section: Staphylococcus Aureus Infection Staphylococcus Aureus Infect...mentioning
confidence: 86%
See 1 more Smart Citation
“…To further systematically understand the immunomodulatory activities that decidua-DEGs and placenta-DEGs were involved in, we performed immune function enrichment analysis by CluGO, which displayed that these DEGs were mainly closely related to macrophage activity, such as affecting macrophage tolerance induction, regulation of macrophage antigen processing and presentation as well as macrophage activation. It has been confirmed that DSC-conditioned medium (CM) can promote macrophage survival and induce typical phenotype of decidual macrophages, and that DSC-CM also inhibit the proinflammatory effects of granulocyte-macrophage colony- (43). From the above studies we could project that DSCs and trophoblasts exerted significant effects on the phenotype and function of decidual macrophage.…”
Section: Staphylococcus Aureus Infection Staphylococcus Aureus Infect...mentioning
confidence: 86%
“…Chen et al. discovered that reduced IL-10 derived from placental villi of URSA patients could activate endoplasmic reticulum stress of macrophages, thereby inhibiting M2 polarization ( 43 ). From the above studies we could project that DSCs and trophoblasts exerted significant effects on the phenotype and function of decidual macrophage.…”
Section: Discussionmentioning
confidence: 99%